2021
DOI: 10.1038/s41409-021-01323-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvage HLA-haploidentical hematopoietic stem cell transplantation with post-transplant cyclophosphamide for graft failure in non-malignant disorders

Abstract: Graft failure requires urgent salvage HSCT, but there is no universally accepted approach for this situation. We investigated T-cell replete haploidentical HSCT with post-transplantation cyclophosphamide following serotherapy-based, radiation-free, reduced intensity conditioning in children with non-malignant disorders who had rejected their primary graft. Twelve patients with primary or secondary graft failure received T-cell replete bone marrow grafts from haploidentical donors and post-transplantation cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…In hematological malignancies, a second haploidentical BMT with reduced-intensity Flu/Cy conditioning or the Baltimore conditioning protocol (PT/Cy) yielded a one-year OS of 56.6% to 66%, with a relapse rate of 23.1% 23 , 24 . However, as a nonmalignant disorder, second transplantation for GF in SAA had a much lower risk of disease relapse; for instance, PT/Cy-based haploidentical transplantation achieved successful engraftment, with a 2-year OS of 91.6% for graft failure in patients with nonmalignant disorders 25 . In this study, a second haploidentical BMT with ATG-containing conditioning achieved a 5-year OS of 75% for SAA patients with GF, indicating that a second haploidentical BMT is a rescue option for urgent cases of graft failure in patients with SAA, with either PT/CY-based or ATG-containing conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In hematological malignancies, a second haploidentical BMT with reduced-intensity Flu/Cy conditioning or the Baltimore conditioning protocol (PT/Cy) yielded a one-year OS of 56.6% to 66%, with a relapse rate of 23.1% 23 , 24 . However, as a nonmalignant disorder, second transplantation for GF in SAA had a much lower risk of disease relapse; for instance, PT/Cy-based haploidentical transplantation achieved successful engraftment, with a 2-year OS of 91.6% for graft failure in patients with nonmalignant disorders 25 . In this study, a second haploidentical BMT with ATG-containing conditioning achieved a 5-year OS of 75% for SAA patients with GF, indicating that a second haploidentical BMT is a rescue option for urgent cases of graft failure in patients with SAA, with either PT/CY-based or ATG-containing conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In general, OS after the second allo-HSCT for graft failure is poor due to high rates of treatment-related mortality associated with infections [ 76 ]. However, recent studies have shown acceptable OS after salvage second allo-HSCT, including CBT or allo-HSCT from haploidentical related donors [ 78 , 79 , 80 , 81 , 82 , 83 ]. No treatments other than salvage second allo-HSCT are established for graft failure with graft rejection, although some investigational drugs, such as an interferon-gamma inhibitor, have been tried [ 76 ].…”
Section: Chimerism Analysis Guiding Management Of Allo-hsct Recipientsmentioning
confidence: 99%
“…However, failure to establish persistent engraftment after HSCT remains a significant factor contributing to morbidity and mortality. Graft failure (GF) is a rare but significant complication following allogeneic HSCT, with varying incidences depending on the type of donor [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%